Perancangan Karakter Buku Anak “What’s Around Ami?” dengan Konsep Antropomorfisme dan Simbolisme Domba dalam Alkitab - Putri, Regina Dian Larasati; Masnuna; Sri Wulandari (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
Children's Storybook "What's Around Ami?" is designed as an educational medium incorporating Biblical values for children aged 4-7 years. Utilizing an anthropomorphic approach and lamb symbolism as its main character, this study aims to create easily understandable character designs. The design methodology includes market observation, interviews with child psychologists and teachers, literature studies on anthropomorphism, and questionnaires to validate character designs. According to child psychologist interviews, children show greater preference for animal characters. This book simplifies complex spiritual concepts while serving as an interactive and engaging solution for parents and educators to teach Christian morals and faith.